Use of botulinum toxin in the management of dystonia in Parkinson’s disease - Anandan, Charenya; Jankovic, Joseph (Frontiers in Neuroscience, 2024)
Botulinum toxin is one of the most potent neurotoxins, but when injected into an overac[ve muscle it can transiently alleviate an involuntary movement, such as dystonia. The primary aim of this ar[cle is to provide a comprehensive review of the various forms of dystonia observed in pa[ents with Parkinson's disease that can benefit from therapeu[c trial of botulinum toxin. Although most of these indica[ons are not supported by randomized controlled clinical trials and, therefore, not approved by the Food and Drug Administra[on, there are many open-label trials suppor[ng a large body of empirical experience tes[fying to the benefits of botulinum toxin treatment in these condi[ons.